Magical rituals in food-quest among the bukidnons of Caratagan, Calinog, Iloilo - De la Peña, Lilian C.
This study focused on magical rituals as observed by the Bukidnons of Central Panay in their economic activities-farming, hunting and fishing. Specifically, it focused on the performance of magical rituals in relation to these economic activities and its effect in the socio-psychological life of the Bukidnons., In analyzing the data gathered, Malinnowski's theory on magic was used. The theory states that whenever man is faced with danger, fear and insecurity, magic crops up (1965:108). A similar view was forwarded by E.E. Evans-Pritchard (1965:43) saying that magic is performed only when man is faced with a situation of emotional turmoil. The data-gathering techniques used were: interviewing key informants, interview schedules of semi-structured and unstructured forms were used. Photographs and voice tapes were also gathered as supplementary data. The study concluded that magical rituals are indeed observed in the Bukidnons economic activities especially in situations fraught with danger. Magical rituals are performed more in farming activity compared to hunting and fishing because it is considered a primary source of food. It is also in this activity where forest, believed to be the spirit-beings abode is disturbed more